Regional Differences in the Medieval Kingdom of Hungary (c. 1500): Brief Description of the NKFI K145924 Project - F. Romhányi, Beatrix; Demeter, Gábor (Historical Studies on Central Europe, 2024)
The objective of this project is to examine and delineate regional differences within the Kingdom of Hungary (the Carpathian Basin in geographical terms) at the end of the Middle Ages. Whereas statistical data comparable to the modern period are unavailable for the Middle Ages, regional inequalities (the economic activity or inactivity of a region) can be approximated using indirect indicators. Given the relatively well-documented settlement network of the Carpathian Basin in the Late Middle Ages and the abundance of available data that can be employed as indicators (proxies), the project will utilise this methodology to construct a database for the time around 1500. The database will be processed in order to make regional differences in the late Middle Ages visible by means of various geospatial methods. Furthermore, comparisons will be made with maps of earlier and later periods, using similar methodologies. In addition, new datasets will be incorporated into the database for the eighteenth century, comprising data from Croatia north of the River Save and church censuses. The project will conclude with the production of a series of maps that will facilitate the identification of long-term processes, including changes over time, as well as their variable and stable elements. Moreover, the identification of regions within the Carpathian Basin that are permanently developed (active) or underdeveloped (inactive) may provide new perspectives for the formulation of regional development strategies in the present.